A New View of the 'Edesö Wreck': identifying the Swedish naval vessel Bodekull, built 1659–1661 and sunk 1678 from written sources. (1st September 2018) - Eriksson, Niklas
Abstract: This article complements the archaeological account of the so‐called 'Edesö Wreck' with archival research that has led to its identification. In 1659 the Swedish King Karl X Gustav ordered a number of vessels for transport of horses and soldiers while at war with Denmark. The king died just a few months later, the war with Denmark was aborted, and the unfinished vessels were rebuilt to serve other purposes. One of these was Bodekull, built under English master shipwright Thomas Day between 1659 and 1661. In October 1678 Bodekull sank in the Stockholm archipelago. Alterations made during construction mentioned in written sources have been noted on the wreck and strengthen the argument for the identification. 摘要: 艾德索沉船的新认识:以文献资料鉴定瑞典军舰 Bodekull 号 (建于1659‐1661年, 沉没于1678年) 本文以文献研究的角度补充对考古记录中称作"艾德索沉船"的认识并使之真正身份得以确认。1659年在与丹麦的交战过程中, 瑞典国王卡尔十世·古斯塔夫下令建造-些用于运-马匹和士兵的船只。但卡尔十世很快在几个月后便去世了, 与丹麦的战争-随即中止。那些未完成的军舰经过重建用做-途。这其中的一-便是 Bodekull 号, 它是由英国造船师Thomas·Day在1659-1661年主持建造的。1678年10月 Bodekull 号沉没于斯德哥尔摩群岛。在文献中所记载的该船建造过程中的诸多变化也在沉船上得以体现, 从而强化了对该船甄别上的证据。 艾德索沉船的新認識:以文獻資料鑒定瑞典軍艦 Bodekull 號 (建于1659‐1661年, 沉沒于1678年) 本文以文獻研究的角度補充對考古記-中稱作"艾德索沉船"的認識並-之真正身份得以確認。1659年在與-麥的交戰過程中, 瑞典國王卡爾十世古斯塔夫下令建造-些用于運-馬匹和士兵的船只。但卡爾十世很快在幾個月後便去世了, 與-麥的戰爭也隨即中止。那些未完成的軍艦經過重建用做-途。這其中的一-便是 Bodekull 號, 它是由英國造船師ThomasDay在1659-1661年主持建造的。1678年10月 Bodekull 號沉沒于斯德哥爾摩群島。在文獻中所記載的該船建造過程中的諸多變化也在沉船上得以體現, 從而強化了對該船甄別上的證據。